Preferential elimination of repeated DNA sequences from the paternal, Nicotiana tomentosiformis genome donor of a synthetic, allotetraploid tobacco - Skalická, K; Lim, K Y; Matyasek, R; Matzke, M; Leitch, A R; Kovarik, A (The New phytologist, 2005)
Nicotiana tabacum (tobacco, 2n = 4x = 48) is a natural allotetraploid combining two ancestral genomes closely related to modern Nicotiana sylvestris and Nicotiana tomentosiformis. Here we examine the immediate consequences of allopolyploidy on genome evolution using 20 S4-generation plants derived from a single synthetic, S0 plant made by Burk in 1973 (Th37). Using molecular and cytogenetic methods we analysed 14 middle and highly repetitive sequences that together total approximately 4% of the genome. Two repeats related to endogenous geminiviruses (GRD5) and pararetroviruses (NtoEPRV), and two classes of satellite repeats (NTRS, A1/A2) were partially or completely eliminated at variable frequency (25-60%). These sequences are all from the N. tomentosiformis parent. Genomic in situ hybridization revealed additivity in chromosome numbers in two plants (2n = 48), while a third was aneuploid for an N. tomentosiformis-origin chromosome (2n = 49). Two plants had homozygous translocations between chromosomes of the S- and T-genomes. * The data demonstrate that genetic changes in synthetic tobacco were fast, targeted to the paternal N. tomentosiformis-donated genome, and some of the changes showed concordance with changes that presumably occurred during evolution of natural tobacco.
Keywords: Polyploidy; biologická evoluce; Genome, Plant; rostlinné viry; křížení genetické; Crosses, Genetic; rozptýlené repetitivní sekvence; genom rostlinný; karyotypizace; DNA virů; Biological Evolution; Karyotyping; DNA, Ribosomal; DNA, Plant; tabák; Tandem Repeat Sequences; DNA rostlinná; ribozomální DNA; DNA, Viral; Plant Viruses; Nicotiana; tandemové repetitivní sekvence; polyploidie; Interspersed Repetitive Sequences